2021
DOI: 10.1007/s11606-020-06432-7
|View full text |Cite
|
Sign up to set email alerts
|

Words Matter: What Do Patients Find Judgmental or Offensive in Outpatient Notes?

Abstract: BACKGROUND: Sharing outpatient notes with patients may bring clinically important benefits, but notes may sometimes cause patients to feel judged or offended, and thereby reduce trust. OBJECTIVE: As part of a larger survey examining the effects of open notes, we sought to understand how many patients feel judged or offended due to something they read in outpatient notes, and why. DESIGN: We analyzed responses from a large Internet survey of adult patients who used secure patient portals and had at least 1 visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“… 9 , 10 One study found that approximately 10% of patients who read their EHR felt judged or offended by their physician’s language. 12 A recent study 7 of physician outpatient notes found that notes about Black patients more often included language indicating disbelief of the patient. However, to our knowledge, ours is the first large-scale analysis quantifying the prevalence of stigmatizing language in the EHR and examining patient and clinician characteristics associated with its use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 , 10 One study found that approximately 10% of patients who read their EHR felt judged or offended by their physician’s language. 12 A recent study 7 of physician outpatient notes found that notes about Black patients more often included language indicating disbelief of the patient. However, to our knowledge, ours is the first large-scale analysis quantifying the prevalence of stigmatizing language in the EHR and examining patient and clinician characteristics associated with its use.…”
Section: Discussionmentioning
confidence: 99%
“…Nationwide, approximately 60% of patients who are offered access to their EHRs viewed their records at least once. 11 Stigmatizing language in records, when viewed by patients, may undermine trust, 12 , 13 which may compromise health outcomes. 14 …”
Section: Introductionmentioning
confidence: 99%
“…These and other issues, warrant further, more nuanced empirical examination and we strongly recommend that research investigate patients’ experiences with accessing mental health notes across a range of settings, including outpatient and inpatient care, and encompassing a wide range of patient populations with different mental health diagnoses. Focused empirical research, including randomized controlled trials, are required to better understand whether access influences objective health outcomes and attendance at visits, and whether patients feel judged or offended by what they read [ 27 ]. There is a need for data among patients with serious mental illness, including schizophrenia, personality disorders, or active suicidality to avoid overgeneralizing current evidence to these populations and use cases.…”
Section: Discussionmentioning
confidence: 99%
“…Focused empirical research is required to better understand whether access influences health outcomes and attendance at visits, and whether patients feel judged or offended by what they read. [25] There is a need for data among patients with serious mental illness, including schizophrenia, personality disorders, or active suicidality to avoid overgeneralizing current evidence to these populations and use cases. Larger scale studies are needed to examine psychiatric clinicians' experiences including emergent concerns with the practice, and potential sources of patient-clinician disagreement.…”
Section: Discussionmentioning
confidence: 99%